Biodegradability of naltrexone-poly(DL) lactide implants in vivo assessed under ultrasound in humans - Hulse, G.; Low, V.; Stalenberg, V.; Morris, N.; Thompson, R.; Tait, Robert; Phan, C.; Ngo, H.; Arnold-Reed, D. (2008)
Ultrasound was used to assess the in vivo biodegradability of a sustained release poly(DL)lactide naltrexone implant in 71 persons previously treated for heroin dependence. We assessed 139 implant sites ranging from 2 to 1808 days post implant. Ultrasound assessment showed that implant tablets were initially well demarcated from each other and from the surrounding tissues. Biodegradation resulted in less demarcated tablets followed by clumping into a single mass-like structure. This mass subsequently dispersed by approximately 1201 days post implant with no implant material visualized by ultrasound. The biodegradation was also assessed by visual clinical examination and palpation of the implant site as well as patient self-report. These measures were generally well correlated with ultrasound results. Clinical assessment of the biodegradation process concluded that the implant changed from 'firm' to 'less firm' and from 'initial square edge' to 'rounded edge' tablets. Collectively, these data provide direct evidence of the in vivo absorption of the Go Medical implant over time, and its biodegradability in humans. © 2007 The Authors.